Interés nacional y equilibrio de poder en las relaciones entre Rusia y México de 1890 a 2010 - Martínez Álvarez, César B. (Revista Mexicana de Política Exterior, 2022)
This article analyzes the factors that have shaped relations between Russia and Mexico over the last century or so; relations that have enjoyed a commendable degree of continuity, despite the immense geographical distances between the two. Based on the premise that the shifting of power on the international arena goes a long way to explaining these ties, the author looks at some of these historic moments and how the governments of Russia and Mexico have interpreted them, with a view to understanding what position each country has occupied in the calculations of the other. In the late 19th century, in the context of rivalry between Europe’s imperial powers, Russia’s naval needs and Mexico’s attempts to project a stable image to the outside world led to a rapprochement, which culminated in the establishing of diplomatic relations in 1890. The transformation of the international system in the wake of World War I helped revive relations between the Soviet Union and Mexico, resulting in the official renewal of diplomatic ties in 1924, which were broken off shortly afterwards in 1930. It would take another world conflict to reestablish diplomatic relations in 1943, but the bipolar dynamic prevalent at the time would prevent these ties from being consolidated until the late Sixties, when a temporary détente fostered closer relations between the two countries. And while the configuration of the new international order is not entirely clear, there are signs of a new rapprochement, which has been more evident on a diplomatic level than in terms of trade, despite the undeniable potential of the latter.